Frequency of Skin Disorders in Type 2 Diabetes Mellitus: A Cross-Sectional Study - Fahad, Razeen; Soban, Madiha; Qasim, Saeeda Fouzia; Aziz, Zubia; Mughal, Faizah; Azim , Fahad (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To determine the frequency of different Skin Manifestations in people with type II Diabetes Mellitus who visit a tertiary care unit in Karachi, Pakistan. Methodology: This cross-sectional study was conducted at Liaquat College of Medical & Dentistry & Darul-Sehat Hospital Karachi from July to Nov 2023. A total of 200 patients with Type II Diabetes Mellitus, attending endocrine & dermatology OPD, were enrolled in this study by using consecutive, non-probability sampling techniques. Demographic parameters were noted. Data was analyzed by SPSS version 20. Results: Two hundred type II Diabetes Mellitus patients (125 Females and 75 Males) were enrolled in the current study. The mean Age of the patients was 49.62± 10 years, and the mean duration of diabetes was between 6.74± 5.55 years. 115 out of 200 (57.5%) patients showed some skin manifestations. The skin manifestations observed were: Infections (bacterial/fungal) (17.38%), Ulcer & gangrene of foot (6.08%), Pruritis (13.33%), Diabetic dermopathy (10.42%), Foot swelling (7.81), Thick and scaly skin(8.68%), Pigmentation including shin spots (7.81%), Cellulitis (6.07%), Acanthosis nigricans (5.2%), Yellow nails (5.2%), Skin tags(3.46%), Psoriasis (3.46%). Conclusion: Participants having Diabetes Mellitus type II are found to have a high frequency of skin manifestations (57.5%). The ratio for females was higher than for males. The majority of participants had only one skin manifestation. A noteworthy association was found between higher HbA1c levels (8.1 to 14%) & the presence of cutaneous manifestations.